Studies on Degradable Polymeric Blends Based on Poly(Lactic Acid) - Singh, Gursewak (My University, 2011)
Melt blending of linear low density polyethylene (LLDPE) and poly(L-lactic acid) (PLLA) was performed in an extrusion mixer with post extrusion blown film attachment with and without compatibilizer i.e. maleic anhydride grafted low density polyethylene. The blend compositions were optimized for tensile properties as per ASTM D 882-91. Based on this, blend sample having 80 wt % LLDPE and 20 wt % PLLA i.e. sample LLDPE 80 and 80 wt % LLDPE, 20 wt % PLLA and 4 parts compatibilizer per hundred parts of resin i.e. sample M-g-L 80/4 were found to have an optimum composition of performance properties; the effect of blending on the mechanical, thermal and morphological characteristics was done. The blends were characterized using mechanical, thermal and morphological behavior. Morphological characteristics of film surface and fracture surface of polymer blends in absence and presence of compatibilizer were examined using scanning electron microscopy. It has been observed that the dispersion of PLLA in LLDPE matrix improved in presence of compatibilizer. FTIR reveals that the presence of compatibilizer shifts carbonyl peak indicating some increase in interaction between LLDPE and PLLA. Thermogravimetric (TG) analysis of blends showed that the M-g-L 80/4 blend has highest thermal stability as compared to LLDPE/PLLA blends of varying composition. The thermogravimetric profile and thermal endurance of these blends were characterized as per ASTM E1641- 07 and E1877-05. The effect of physical aging on mechanical and thermal properties of these blends was evaluated. PLLA showed the highest Arrhenius activation energy, relative thermal index and strongest thermal endurance of all samples followed by M-g- L 80/4 and LLDPE 80. The thermo-oxidation coefficient improved with addition of xx compatibilizer in the blends. With increasing pH, hydrolytic degradation of the blend films increased, while both the tensile strength and the elongation at break of the blend films decreased. The degradation study under different pH of soil composting indicates that alkaline conditions and presence of compatibilizer favors the degradation. From this studies it can be concluded that such films based on LLDPE/PLLA with 20% of PLLA and in presence of compatibilizer (4phr) may find application in the field of packaging as biodegradable material.
Ph.D. (CHED)
Keywords: PLLA; LLDPE; Degradation; Blends